The reliability of functional movement screening and in-season changes in physical function and performance among elite rugby league players - Waldron, M.; Gray, A.; Worsfold, P.; Twist, C. (The Journal of Strength and Conditioning Research, 2016)
This study aimed to (a) assess the reliability of the functional movement screening (FMS) protocol and (b) to establish changes in both FMS and tests of physical performance throughout a season. The reliability of the FMS components (12 in total) was assessed through a nonparametric statistical approach, based on 2 trials, separated by 1 week. Score on the FMS, strength (3 repetition maximum full squat, 1 repetition maximum [1 RM] bench press), running speed (10 and 40 m), and jump height of 12 elite male under-19 rugby league players was monitored at pre-, mid-, and late-season periods. There was no bias (p > 0.05) found between trials for the FMS, with the majority of components reaching 100% "perfect agreement," reflecting the good reliability of the FMS tool. There were no effects (p > 0.05) of season stage on any of the FMS components; however, an improvement (p = 0.05) between the pre- and both mid- and late-season periods was apparent in every component of fitness, such as 1 RM bench press (112.92 ± 24.54 kg; 125.83 ± 21.41 kg; 125.98 ± 24.48 kg) and 40-m sprint time (5.69 ± 0.35 seconds; 5.62 ± 0.31 seconds; 5.64 ± 0.27 seconds). Our findings demonstrate that the FMS can be reliably administered to elite rugby league players but will not change in accordance with physical performance across a competitive season. Our findings should not necessarily deter practitioners from using the FMS but begin to question the specific qualities that are being assessed through its administration.